Analisis Makna Konotatif Pada Puisi “Cintaku Jauh di Pulau” Karya Chairil Anwar: Kajian Semantik - Kartini, Rismaniar; Zahrani, Nadilah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The aim of the researcher in this study is to describe the connotative meaning contained in Chairil Anwar's poem entitled